Attitude toward Space: Hidden Identity in Contemporary Asian Vernacular Architecture - Phattanawasin, Srisak (Journal of Architectural/Planning Research and Studies (JARS), 2002)
In the past two decades, significant contextual factors such as the spread of globalization and consumerism, the growth of rapid urbanization, the flux of information technology, and the increase of tourism industry have inevitably evoked the awareness of cultural identity, traditional heritage, and indigenous wisdom in the Asian countries. Also the role of architecture in place-making and in the quest for localization ideology has been extensively debated. It is crucial to examine how the vernacular archetypes–manifestations of formal characteristic and spatial organization–can be reinterpreted and suitably applied to the contemporary social and cultural context. The adaptation of iconographic elements has been mostly seen in the developments of architectural transformation. However, the ‘quality of spatial organization’ seems to be ignored and hardly be addressed in contemporary buildings, though this quality reflects the social and cultural values and lifestyles. This article employs collective observations of attitude toward space via spatial qualities such as hierarchy, transition, enclosure, viewing, as well as lighting. By comparing case studies of contemporary Asian architecture, this review focuses on the above spatial qualities as the ‘hidden identity’ in vernacular way of life. This would reinforce the valuable identity in the course of the interacting cultures of Asian societies in transition. It might also be an invigorating approach toward the typological and ideological development of contemporary Asian vernacular architecture in the contextual changes.